Penerapan Model Markowitz dalam Memperoleh Portofolio Optimal di Pasar Saham IDX30 - Ridwanudin, Oce; Sari, Maya (Image : Jurnal Riset Manajemen, 2023)
Investment in financial market is inextricably linked to risk. The risk cannot be eliminated, but indeed it can be minimized. By using Markowitz model, investor can gain optimal result while taking on acceptable risk. This study intends to examine the findings of optimal portfolio construction using Markowitz model on IDX 30. The method was quantitative descriptive. The population was all companies listed on IDX 30. Then, there were three companies chosen as the sample. The investigation of the three stocks yielded two efficient portfolios. First were the stocks of PT Bank Negara Indonesia, Tbk. and PT Astra International. The second was stocks of PT Bank Negara Indonesia, Tbk. and PT Adaro Energy Indonesia, Tbk.  Each stock provided a return of 1.03 % with the risk level of 7.75%, and 4.4% with the risk level of 8.49%. The conclusion is that by using these two portfolios, investor can get optimal expected returns with the degree of risk comparable to individual equities. Thus, it is suggested for the investor to apply the calculation of Markowitz model on Indonesia Stock Exchange over a longer period than the one used in this study. It is also suggested for them to select the portfolio in accordance to their preferences.